Multimedialny świat dzieci a świadomość rodziców - Kobiałka, Andrzej (Annales Universitatis Paedagogicae Cracoviensis Studia Paedagogica, 2021)
The article is an attempt to define and term what is parents’ awareness in the context of multimedia children functioning in the virtual world.Own research concerns the perception of parents from Myślenice commune on the children multimedia world in preschool age. Through the analysis of the research, the author interprets and tries to systematize what are the mature attitudes of parents. In addition, author’s intention was that parents wisely and consciously was creating process of upbringing, their children and at the same time they did not insulate or ruled out form virtual world. Summary and the final conclusions end this article.